Insight Into the Fracture of the Soul: the Poetics of Isaković’s Stories Between the Lyrical Setting and Dramatic Grotesque - Enes Duraković (Društvene i Humanističke Studije, 2018)
Abandoning experiences of the traditional Bosnian narrative prose, Alija Isaković composes the storyusing a dynamic synthesis, transformations and mixtures of different forms. Therefore, his stories need to be interpreted in a wider cultural context, noticing, along with general characteristics of the BiH literature from that time that wasconsciously open towards the experience of the modern European culture, particularities of the author’s expression unsusceptible to the rules of the general literary forms. His novellas were composed in the moments of bizarre  misunderstandings of the individual with the world and with the self, occurring when the fragile balance of tranquility is disturbed in the soul as well as in the matter, and the fracture that disseminates the individual incapable of maintaining the integrity of the self appears. In these writings, the ideological contamination of the text disappears, the realistically mediated image of social reality disseminates, and the collective subject vanishes, while, in accordance with the existentialist juncture of perception, a dispersive image of an individual area of awareness appears without the metaphysical shelter and illusions of social utopia.